Efectividad y eficacia de la anestesia raquídea en colecistectomía laparoscópica en el Hospital Regional de Loreto “Felipe Santiago Arriola Iglesias” durante el periodo junio 2022 a junio 2023 - Infante Berrú, Carolina Stephany (2024)
Spinal anesthesia is currently an alternative in laparoscopic surgery since it allows an adequate anesthetic block with adequate muscle relaxation of the abdominal wall during surgery, it also allows multi-parameter monitoring of the patient, keeping it hemodynamically stable, reducing the complications of general anesthesia. OBJECTIVE: To determine the effectiveness and efficiency of spinal anesthesia in patients underwent laparoscopic cholecystectomy at the Regional Hospital of Loreto "Felipe Santiago Arriola Iglesias" during the period June 2022 to June 2023. METHODS: Prospective and randomized observational study at the "Felipe Santiago Arriola Iglesias" Regional Hospital of Loreto during the period June 2022 to June 2023, the sample is made up of 47 patients undergoing spinal anesthesia for laparoscopic cholecystectomy, through the administration of anesthesia. spinal with bupivacaine 15mg and fentanyl 20ug; the variability of HR, PA, MAP, and SAT02 will be evaluated in addition to muscle relaxation and identify the main intraoperative complications.